The Role Of Elderly Sexuality On Musculoskeletal Disorders (MSDs): Bibliometric Studies - Prastowo, Bayu; Windayati, Aluf Mumtaziah (STIKES Telogorejo Semarang, 2022)
The United Nations' annual report states that the projection of the elderly population continues to increase. The projected population age is a crucial indicator in the ageing process. People who enter the ageing phase experience soft tissue pain and musculoskeletal disorders at a rate of 95%. However, sexual activity can reduce physiological and psychological disorders through the hormonal system. So these events are included in the sustainable development agenda. Research objectives : The purpose of this research is to analyze the effects of sexual activity on musculoskeletal disorders. Methodology : This study uses a bibliometric method by adopting a chart mapping of preferred reporting items for systematic reviews and meta-analysis. Research data obtained from search engines must be published or perish. Analysis of metadata text function using VOSviewer. Result : The publication of 64 articles in the last five years was dominated by Scopus compared to PubMed. The research topic updates include sexual sphere characteristics and health care needs. Descriptively, the metadata states that sexual activity in the elderly influences musculoskeletal disorders. Conclusion : However, sexual activity is carried out in a broad sense. This study only analyzes the patterns displayed by VOSviewer with a systematic review. Research conducted without confirming whether it uses a qualitative or quantitative approach.